The impact of digital platforms on english learning in ecuadorian public primary schools - Gavilanes Cuesta , María Eugenia (2025)
"Learning English as a second language has always been key worldwide because it is a means of communication and connection with other cultures and nationalities, hence its importance of starting to learn it from an early age. This literature review allows us to scientifically justify the topic presented and highlights the use of digital platforms as a methodological and pedagogical mediator in the acquisition of English as a second language in children ranging from 6 to 12 years of age. Therefore, the effectiveness of technological integration in the sector of public education has the potential to offer students interactive and engaging opportunities that encourage meaningful learning of English while promoting language skills through active participation and motivation as a result. However, the socio-economic factor and the lack of technological resources in public schools and families make a difference in the education and learning of this language, which is why state support is essential, as well as the professional development and constant training of teachers in the use of virtual platforms such as Microsoft Teams, Google Meet and Zoom among others but also new technologies for success in the acquisition of the English language."